PENERAPAN AKUNTANSI NIRLABA BERDASARKAN ISAK 35 (STUDI KASUS PADA PERBAKIN KOTA PONTIANAK) - Fakhri'alauddin, Muhammad (Jurnal KIAFE, 2023)
This study aims to find out how financial management is in non-profit organizations and see how the records are related to the standards issued by the Indonesian Institute of Accountants (IAI) in financial reporting for non-profit organizations, namely ISAK 35 in Perbakin, Pontianak City. This study uses a qualitative method. Data was collected using interviews, documentation and literature studies. The interview was conducted with the treasurer of the organization. The results of this study indicate that Perbakin Pontianak has not yet recorded financial reports in accordance with ISAK 35. This is because they do not understand financial standards and the management is still based on previous financial reports.